The Influence of Social Environment, Financial Literacy, and Lifestyle on Family Financial Planning Among Housewives - Fitriani, Andi St.; Mas'ud, Masdar; Nurpadilla, Nurpadilla; Budiandriani, Budiandriani (Journal of Economic Education and Entrepreneurship Studies, 2024)
This research rigorously aimed to explore the impact of the social environment, financial literacy, and the lifestyle of housewives on the dynamics of family financial planning in Kalukuang, Tallo, Makassar. The research undertaken is of a quantitative nature. It employs a combination of primary and secondary data, utilizing methodologies such as questionnaires and literature reviews for data collection. The research sample comprises 70 individuals engaged in domestic management. The methods applied for data analysis encompass validity and reliability assessments, classical assumption evaluations, and multiple regression analysis, which incorporates the coefficient of determination test, T test, and F test, all executed using SPSS version 26. The findings of this research revealed that: (1) The social environment (X1) exerted a positive and significant impact on family financial planning in Kalukuang, Tallo, Makassar; (2) Financial literacy (X2) demonstrated a positive and significant influence on family financial planning in Kalukuang, Tallo, Makassar; (3) Lifestyle (X3) also had a positive and significant effect on family financial planning in Kalukuang, Tallo, Makassar; (4) The combined influence of the social environment (X1), financial literacy (X2), and the lifestyle of housewives (X3) resulted in a positive and significant effect on family financial planning in Kalukuang, Tallo, Makassar.